HÁZIRGI QARAQALPAQ TILINDE KÓP KOMPONENTLI DIZBEKLI QOSPA GÁPLERDIŃ QOLLANÍLÍW ÓZGESHELIKLERI - Mangitbaeva, Z.U. (SCIENCE and SOCIETY, 2025)
The article focuses on the study of the theoretical foundations of the study of multicomponent complex sentences, their structural and semantic analysis, application, types and issues of the formation of syntactic structures.